2006
DOI: 10.1158/0008-5472.can-06-0160
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Costimulation Provided through a CD19-Specific Chimeric Antigen Receptor EnhancesIn vivoPersistence and Antitumor Efficacy of Adoptively Transferred T Cells

Abstract: Chimeric antigen receptors (CAR) combine an antigenbinding domain with a CD3-Z signaling motif to redirect Tcell specificity to clinically important targets. First-generation CAR, such as the CD19-specific CAR (designated CD19R), may fail to fully engage genetically modified T cells because activation is initiated by antigen-dependent signaling through chimeric CD3-Z, independent of costimulation through accessory molecules. We show that enforced expression of the fulllength costimulatory molecule CD28 in CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
383
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(404 citation statements)
references
References 51 publications
16
383
2
3
Order By: Relevance
“…2) [18]. Subsequent studies demonstrated that activation of T cells engineered to express first-generation CARs was incomplete and that T cells modified with second-or third-generation CARs that incorporated, respectively, one or more intracellular costimulatory signaling domains derived from CD28, 41BB, OX40, DAP10, ICOS, or CD27 possessed greater proliferative capacity, cytokine secretion, and anti-tumor activity than their first generation counterparts [27][28][29][30][31][32][33][34]. The importance of costimulation was confirmed in a clinical trial in which patients with B cell non-Hodgkin lymphoma were treated with T cells modified to express a CD19-specific CAR that incorporated either a CD28 costimulatory domain or no costimulation [35].…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…2) [18]. Subsequent studies demonstrated that activation of T cells engineered to express first-generation CARs was incomplete and that T cells modified with second-or third-generation CARs that incorporated, respectively, one or more intracellular costimulatory signaling domains derived from CD28, 41BB, OX40, DAP10, ICOS, or CD27 possessed greater proliferative capacity, cytokine secretion, and anti-tumor activity than their first generation counterparts [27][28][29][30][31][32][33][34]. The importance of costimulation was confirmed in a clinical trial in which patients with B cell non-Hodgkin lymphoma were treated with T cells modified to express a CD19-specific CAR that incorporated either a CD28 costimulatory domain or no costimulation [35].…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…68  The first-generation CAR utilized only CD3z to activate T cells without incorporating a co-stimulatory domain, the in vivo anti-tumor efficacy of these cells is poo. 9 Second-generation CAR-T cells, which generally utilize CD28 or 4-1BB as a co-stimulatory signal, have shown surprising efficacy in leukemia patient. 2,6,10 Nonetheless, the efficacy of CAR-T cells against solid tumors remains poor and uncertain, perhaps due to factors that suppress T cell responses in the tumor microenvironmen.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinically, the Pmel-1 TCR transgenic murine tumor model recapitulates many features of the clinical experience and is particularly suitable, since the TCR transgenic T cells are specific for a self antigen, as opposed to a strong xenoantigen. Pmel-1 T cells bear a transgenic TCR that recognizes the gp100 [25][26][27][28][29][30][31][32][33] H-2D b -restricted epitope of the melanoma tumor antigen gp100, which is expressed by murine B16 melanomas [31] and GL261 gliomas [38]. Adoptive transfer of Pmel-1 CD8 + T cells alone into lymphodepleted C57BL/6 mice has no impact on the growth of established subcutaneous B16 tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive transfer of Pmel-1 CD8 + T cells alone into lymphodepleted C57BL/6 mice has no impact on the growth of established subcutaneous B16 tumors. Regression of established B16 occurs only when the adoptive transfer is complemented by vaccination with recombinant viral vectors expressing human gp100 or syngeneic dendritic cells (DC) pulsed with the human gp100 [25][26][27][28][29][30][31][32][33] (hgp100 [25][26][27][28][29][30][31][32][33] ) peptide, followed by systemic administration of high doses of IL-2 or IL-15 as sources of helper cytokines [1,14,15,31,32,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation